'To what extent you have to be satisfied with your situation there … ': August(us) Petermann in Britain, 1845–1854. Issue Volume 74:Issues 2(2022) (3rd July 2022) - Demhardt, Imre Josef
ABSTRACT: After his apprenticeship with Heinrich Berghaus in Potsdam, August(us) Petermann worked from 1845 to 1847 for W. & A. K. Johnston in Edinburgh to assist in the production of the English version of Berghaus's Physikalischer Atlas . In June 1847, Petermann became a freelance cartographer in London focusing on innovative maps of population, infrastructure, hydrography and other themes in Britain, as well as on exploration maps of Africa and the Arctic. From 1853, his commercial ties with Justus Perthes's Geographische Anstalt intensified, and in 1854 a now professionally well-rounded Petermann moved to Gotha. This article, written to commemorate the bicentenary of his birth, is a comprehensive appraisal of Petermann's nine years in the United Kingdom. It is posited that his work there was both formative and ultimately essential to the innovations in cartography and geography that he encouraged in his journal Petermanns Mittheilungen from 1855 on. The article is complemented by the first thoroughly revised carto-bibliography and bibliography of his oeuvre in more than a century.